The Revised Statutes of the State of Florida 782 (W.A. Blount et al. eds., 1892) - (:unkn) unknown (My University, 1885)
Tit. 2, art. 5, § 2421: Prohibited the concealed carry of any dirk, pistol, or other weapon. Violators imprisoned not exceeding six months or fined not exceeding one hundred dollars.
Keywords: CARRY - CONCEALED